How do you pay? The role of incentives at the point-of-sale - Carlos Arango; Kim P. Huynh; Leonard Sabetti (European Central Bank (ECB), 2011)
This paper uses discrete-choice models to quantify the role of consumer socioeconomic characteristics, payment instrument attributes, and transaction features on the probability of using cash, debit card, or credit card at the point-of-sale. We use the Bank of Canada 2009 Method of Payment Survey, a two-part survey among adult Canadians containing a detailed questionnaire and a three-day shopping diary. We find that cash is still used intensively at low value transactions due to speed, merchant acceptance, and low costs. Debit and credit cards are used more frequently for higher transaction values where safety, record keeping, the ability to delay payment and credit card rewards gain prominence. We present estimates of the elasticity of using a credit card with respect to credit card rewards. Reward elasticities are a key element in understanding the impact of retail payment pricing regulation on consumer payment instrument usage and welfare.
Keywords: E41; C35; C83; 330; credit card rewards; discrete-choice models; Retail payments